Positive plate and lithium ion secondary battery
By blending lithium manganese oxide and ternary materials into the positive electrode material of lithium-ion secondary battery and using carbon nanotubes as conductive agents, it is solved that existing batteries are difficult to take into account the high energy density, good safety performance, and excellent high-temperature cycling and rate performance. The problem of achieving higher battery performance and lower costs.
Patent Information
- Application Number
- CN202411635900.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The existing lithium-ion secondary battery positive electrode materials are difficult to take into account the problems of high energy density, good safety performance, and excellent high-temperature cycling and rate performance.
A blended positive electrode active material including lithium manganate material and ternary material is used, combined with carbon nanotubes as conductive agents, and a high-pressure density positive electrode sheet is formed by regulating the particle size and structural design of the material.
The energy density, safety performance, thermal stability and circulation performance of the battery are improved, the contact between lithium manganese oxide and electrolyte is reduced, manganese dissolution is inhibited, and conductive properties are enhanced.
Smart Images

Figure CN119480904A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode sheet and a lithium-ion secondary battery. Background Art
[0002] In new energy vehicles, battery costs account for about 42% of the overall cost, and positive electrode materials account for about 40% of the battery cost. It can be said that positive electrode materials are an important variable affecting the cost of new energy vehicles.
[0003] At present, the commercialized positive electrode active materials of lithium-ion secondary batteries mainly include lithium manganese oxide, lithium cobalt oxide, and two-element or three-element materials obtained by replacing part of the cobalt in lithium cobalt oxide with nickel or manganese. Compared with the high cost of lithium cobalt oxide, lithium manganese oxide and three-element materials have price advantages. In addition, lithium manganese oxide batteries have almost no gas precipitation during storage and charging and discharging, and have good high temperature resistance. However, the only drawback is that the compaction density of lithium manganese oxide is low, which is not conducive to the cycle performance of the battery. Although the energy density of ternary materials is higher, they are also prone to thermal runaway at high temperatures, resulting in poor safety performance of the battery. It can be seen that the single positive electrode active materials have their own advantages and disadvantages, and cannot better meet the growing multifunctional requirements of different power products. Summary of the invention
[0004] The present application provides a positive electrode sheet, which aims to solve to a certain extent the problem that the existing lithium-ion secondary batteries containing a single positive electrode active material cannot have high energy density, good safety performance, and excellent high-temperature cycle and rate performance.
[0005] The present application also provides a lithium-ion secondary battery comprising the above-mentioned positive electrode sheet.
[0006] According to an embodiment of the present application, in a first aspect, the present application provides a positive electrode sheet, comprising a positive electrode current collector and a first positive electrode active material layer disposed on at least one side surface of the positive electrode current collector, wherein the first positive electrode active material layer comprises a first positive electrode active material, a conductive agent and a binder;
[0007] The first positive electrode active material includes a lithium manganate material and a ternary material. The particle size A of the first positive electrode active material satisfies: 2.14≤A≤12.5 and A=Dv99 / Dv50 PAM , among which, Dv50 PAM It is the particle size corresponding to the cumulative volume distribution percentage of the first positive electrode active material reaching 50%, 2μm≤Dv50 PAM ≤7μm; Dv99 is the particle size corresponding to when the cumulative volume distribution percentage of the first positive electrode active material reaches 99%, 15μm≤Dv99≤25μm;
[0008] The conductive agent includes carbon nanotubes, and the length L of the carbon nanotubes satisfies 5 μm≤L≤30 μm.
[0009] In some optional embodiments, based on the mass of the first positive electrode active material, the content of the lithium manganate material is 10%-60%, preferably 30%-60%.
[0010] In some optional embodiments, the chemical formula of the lithium manganese oxide material is LiNi a Mn 2-a O 4 , 0≤a≤0.2.
[0011] In some optional embodiments, the lithium manganese oxide material includes a single crystal lithium manganese oxide material.
[0012] In some optional embodiments, based on the mass of the first positive electrode active material, the content of the ternary material is 40%-90%, preferably 40%-70%.
[0013] In some optional embodiments, the chemical formula of the ternary material is LiNi x Co y Mn 1-x-y O 2 , 0.8≤x<1,0 <y<0.2。
[0014] In some optional embodiments, the ternary material comprises a single crystal ternary material.
[0015] In some optional embodiments, based on the mass of the first positive electrode active material layer, the content of the carbon nanotubes is 0.1%-1.2%, preferably 0.1%-0.5%.
[0016] In some optional embodiments, the carbon nanotube has a diameter of 7 nm-11 nm.
[0017] In some optional embodiments, the specific surface area of the carbon nanotubes is 200 m 2 / g-280m 2 / g.
[0018] In some optional embodiments, the XRD spectrum of the first positive electrode active material has a characteristic peak P at a position of 2θ of 35°-38°. 1 and P 3 And the characteristic peak P appears at the position of 2θ 42°-46° 2 and P 4 , P 1 , P 2 , P 3 and P 4The peak intensities of I 1 ,I 2 ,I 3 and I 4 , and satisfy: 0.05≤I 1 ≤0.2,0.05≤I 2 ≤0.18, 0.1≤I 3 ≤0.25, 0.2≤I 4 ≤0.5.
[0019] In some optional embodiments, the positive electrode sheet further includes a plurality of positive electrode ears and an insulating layer, wherein the plurality of positive electrode ears are spaced apart along the length direction of the positive electrode sheet and protrude from the positive electrode current collector; in the width direction of the positive electrode sheet, the insulating layer is arranged along the side of the positive electrode sheet, and the insulating layer and the plurality of positive electrode ears are located on the same side of the positive electrode sheet, the insulating layer is adjacent to but not overlapping with the first positive electrode active material layer, the insulating layer is also arranged at a partial area of the positive electrode ear near the connection between the positive electrode ear and the positive electrode current collector, and an empty foil area is left at the head of the positive electrode ear.
[0020] In some optional embodiments, along the length direction of the positive electrode ear, the length of the insulating layer on the positive electrode ear is 4 mm ≥ h 1 ≥2mm.
[0021] In some optional embodiments, the width of the insulating layer on the positive electrode current collector is 4 mm ≥ h 2 ≥0.5mm.
[0022] In some optional embodiments, based on the mass of the insulating layer, the insulating layer includes 70%-98% boehmite, 0%-20% alumina and 2%-10% binder.
[0023] In some optional embodiments, the positive electrode sheet further includes a second positive electrode active material layer, the first positive electrode active material layer is located between the positive electrode collector and the second positive electrode active material layer; the second positive electrode active material layer includes a ternary material.
[0024] In some optional embodiments, the volume median diameter D of the lithium manganate material in the first positive electrode active material layer is 1 The volume median diameter D of the ternary material in the second positive electrode active material layer 2 The ratio is 1.6-7.5, and D 1 8μm-15μm, D 2 2μm-5μm.
[0025] In some optional embodiments, the second positive electrode active material layer includes a ternary material and a high-temperature lithium manganese oxide material, and the first positive electrode active material layer includes a capacity-type lithium manganese oxide material.
[0026] In some optional embodiments, the ratio of the thickness of the second positive electrode active material layer to the thickness of the first positive electrode active material layer is 0.12-0.4.
[0027] In some optional embodiments, the thickness of the first positive electrode active material layer is 40 μm-100 μm.
[0028] In some optional embodiments, the thickness of the second positive electrode active material layer is 12 μm-16 μm.
[0029] According to an embodiment of the present application, in a second aspect, a lithium-ion secondary battery is provided, comprising a negative electrode sheet, a separator, an electrolyte, and the positive electrode sheet described in the first aspect of the present application.
[0030] In some optional embodiments, the negative electrode sheet includes a negative electrode active material, the negative electrode active material includes graphite with a carbon coating layer; the graphitization degree of the graphite is ≥ 93%, and / or the volume median diameter of the graphite is Dv50 G The thickness of the carbon coating layer is 10 μm-25 μm, and / or the thickness of the carbon coating layer is 0.1 mm-1 mm.
[0031] In some optional embodiments, the lithium-ion secondary battery includes a multi-electrode winding structure.
[0032] In some optional embodiments, the negative electrode active material further comprises a silicon-based material, and the content of the silicon-based material is 0-10% based on the mass of the negative electrode active material.
[0033] In some optional embodiments, the silicon-based material is SiC and / or SiO, the volume median diameter of the SiC is 5 μm-12 μm, and / or the volume median diameter of the SiO is 4 μm-10 μm.
[0034] In some optional embodiments, the electrolyte includes propyl propionate, and the content W of the propyl propionate is 5%-60% based on the mass of the electrolyte, and satisfies: R = Dv50 G *W / Dv50 PAM , 0.07≤R≤7.5, 2μm≤Dv50 PAM ≤7μm; Dv50 G 10μm-25μm.
[0035] In some optional embodiments, the diaphragm includes a base film, a ceramic layer and a coating layer are stacked on one surface of the base film, and the ceramic layer is located between the base film and the coating layer.
[0036] In some optional embodiments, the coating layer includes polyvinylidene fluoride and polymethyl methacrylate in a mass ratio of 1:9-9:1, and the thickness H of the coating layer and the area ratio S of the coating layer on the base film satisfy: Q=H / S, 0.7≤Q≤15, H is 0.5μm-3μm, and S is 20%-70%.
[0037] In some optional embodiments, the S is 30%-40%.
[0038] In some optional embodiments, the volume median diameter of the polyvinylidene fluoride is 0.3 μm-2.5 μm.
[0039] In some optional embodiments, the volume median diameter of the polymethyl methacrylate is 0.1 μm-0.2 μm.
[0040] In some optional embodiments, the porosity of the separator is 40%-50%.
[0041] In some optional embodiments, the air permeability of the diaphragm is 70sec / 100cc-170sec / 100cc.
[0042] In some optional embodiments, the pore size of the base membrane is 32nm-58nm.
[0043] In some optional embodiments, the pore size of the base membrane is 45nm-58nm.
[0044] In some optional embodiments, the ceramic layer includes boehmite and / or alumina.
[0045] In an optional embodiment, based on the mass of the electrolyte, the electrolyte includes 10%-20% of lithium salt, 60%-80% of organic solvent and 1%-5% of additives.
[0046] The technical solution of this application has the following advantages:
[0047] The positive electrode sheet provided in the present application comprises a positive electrode current collector and a first positive electrode active material layer disposed on at least one side surface of the positive electrode current collector, wherein the first positive electrode active material layer comprises a first positive electrode active material, a conductive agent and a binder; the first positive electrode active material (referred to as a mixed material) comprises a ternary material and a low-cost lithium manganate material, and the conductive agent comprises carbon nanotubes. The present application regulates the particle size of the positive electrode active material in the positive electrode sheet and the length L of the carbon nanotubes to satisfy the following conditions:
[0048] 2.14≤A≤12.5, A=Dv99 / Dv50 PAM ; 5μm≥L≥30μm.
[0049] First, it can ensure that the large particles of lithium manganese oxide material and the small particles of ternary material are evenly distributed in the positive electrode sheet after rolling, and the positive electrode sheet has a high compaction density (≥3.25g / cm 3 ), improve the energy density of the battery;
[0050] Secondly, the structure of lithium manganese oxide is more stable than that of ternary materials. Lithium manganese oxide can effectively suppress the problem of flammable runaway of ternary materials, improve the thermal stability of mixed materials, and optimize the safety performance of batteries.
[0051] Thirdly, the mixing of ternary materials with lithium manganese oxide reduces the contact between lithium manganese oxide and the electrolyte, which can inhibit the dissolution of manganese to a certain extent and improve the high-temperature cycle and rate performance of the battery.
[0052] Fourthly, the present application uses carbon nanotubes as conductive agents, regulates the length of the carbon nanotubes, increases the ionic conductivity of the positive electrode sheet, and improves the battery cycle performance, which is crucial to the stability of the electrode material during the charge and discharge process and the long-term cycle life.
[0053] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0055] Figure 1 It is a SEM image of the cross section of the positive electrode sheet in one embodiment of the present application.
[0056] Figure 2 This is a SEM image of the surface of the positive electrode sheet in one embodiment of the present application.
[0057] Figure 3 It is a plan view of a positive electrode sheet in one embodiment of the present application.
[0058] Figure 4 It is a SEM image of the surface of the negative electrode sheet in one embodiment of the present application.
[0059] Figure 5It is an XRD spectrum of the negative electrode active material in one embodiment of the present application.
[0060] Figure 6 is a SEM image of a separator in one embodiment of the present application.
[0061] Figure 7 It is a comparison chart of the XRD spectra of the positive electrode active materials in Example 1 of the present application and Comparative Example 1.
[0062] Figure 8 yes Figure 7 An enlarged view of a certain part.
[0063] Fig. 9 yes Figure 7 Another partial enlargement of .
[0064] Fig.10 It is a comparison chart of the cycle retention rate curves of Example 1 of the present application and Comparative Examples 1-2.
[0065] The reference numerals are described as follows:
[0066] 1. Positive electrode active material layer; 2. Insulating layer; 3. Positive electrode ear. DETAILED DESCRIPTION
[0067] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.
[0068] In the description of the present application, it should be noted that the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance. In the technical solution of the present application, the terms "blended material" and "first positive electrode active material" have the same meaning and can be replaced with each other.
[0069] " Scope " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way includes endpoint values, and can be combined arbitrarily, that is, any lower limit can form a scope with any upper limit combination. For example, if the scope of 1-100 is listed for a specific parameter, it is understood that the scope of 1-100 is expected. In addition, if the minimum range values 1 and 2 listed, and if the maximum range values 3,4 and 5 are listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.
[0070] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0071] In addition, the technical features involved in the different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.
[0072] In order to solve the technical problems existing in the above-mentioned related technologies, according to the first aspect of the present application, a positive electrode sheet is provided, comprising a positive electrode current collector and a first positive electrode active material layer arranged on at least one side surface of the positive electrode current collector, wherein the first positive electrode active material layer comprises a first positive electrode active material, a conductive agent and a binder;
[0073] The first positive electrode active material includes a lithium manganate material and a ternary material. The particle size A of the first positive electrode active material satisfies: 2.14≤A≤12.5 and A=Dv99 / Dv50 PAM , among which, Dv50 PAM It is the particle size corresponding to the cumulative volume distribution percentage of the first positive electrode active material reaching 50%, 2μm≤Dv50 PAM ≤7μm; Dv99 is the particle size corresponding to when the cumulative volume distribution percentage of the first positive electrode active material reaches 99%, 15μm≤Dv99≤25μm;
[0074] The conductive agent includes carbon nanotubes, and the length L of the carbon nanotubes satisfies: 5 μm≤L≤30 μm.
[0075] The present application mixes low-cost lithium manganese oxide material into the ternary material as the first positive electrode active material. When the particle size A satisfies the above relationship, it can ensure that the large particles of lithium manganese oxide material and the small particles of ternary material are evenly distributed in the positive electrode sheet after rolling, which has the following advantages:
[0076] First, it can ensure that the positive electrode sheet has a higher compaction density (≥3.25g / cm 3 ), improve the energy density of the battery;
[0077] Secondly, the structure of lithium manganese oxide is more stable than that of ternary materials. Lithium manganese oxide can effectively suppress the problem of ternary materials being flammable and out of control, improve the thermal stability of mixed materials, improve overcharge and furnace temperature performance, and optimize the safety performance of the battery.
[0078] Thirdly, the mixing of ternary materials with lithium manganese oxide reduces the contact between lithium manganese oxide and the electrolyte, which can inhibit the dissolution of manganese to a certain extent and improve the high-temperature cycle and rate performance of the battery.
[0079] At the same time, the present application uses carbon nanotubes as a conductive agent, and regulating the length L of the carbon nanotubes within the above range can significantly improve the conductivity and cycle stability of the battery. This is because if the length of the carbon nanotubes is too long (> 30 μm), the carbon nanotubes are prone to entanglement, resulting in difficulty in combining with the positive electrode active material and unstable internal structure of the positive electrode sheet; if the length of the carbon nanotubes is too short (< 5 μm), it is difficult to form a three-dimensional conductive network, the conductivity is poor, and the stability and long-term cycle life of the electrode material are affected.
[0080] by Figure 1 Take as an example to illustrate the positive electrode structure of the present application. Figure 1 As shown, the middle black line is the positive electrode current collector, and the first positive electrode active material layer is set on the two sides of the positive electrode current collector. In the positive electrode active material layer, the dark gray patch is the lithium manganese oxide material, and the light gray patch represents the ternary material. It can be seen that the large particles of lithium manganese oxide material and the small particles of ternary material are evenly distributed. As an example, the volume median diameter Dv50 of the first positive electrode active material PAM For example, it can be 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, etc., or within the range formed by any two of the above values. The Dv99 of the first positive electrode active material can be, for example, 15μm, 17.5μm, 20μm, 22.5μm, 25μm, etc., or within the range formed by any two of the above values. The Dv99 and Dv50 of the first positive electrode active material are PAM The value of the ratio A can be 2.14, 3, 5, 7, 9, 11, 12.5, etc. or within the range formed by any two of the above values.
[0081] See also Figure 2 The rod-like structures in the figure are carbon nanotubes, which form a connected conductive network. As an example, the length L of the carbon nanotubes can be 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, etc., or within a range of any two of the above values.
[0082] The particle size of the sample in the present application can be measured by a conventional laser particle size analyzer, and the length of the carbon nanotube can be measured by a scanning electron microscope (SEM).
[0083] In some embodiments, based on the mass of the first positive electrode active material, the content of the lithium manganate material is 10%-60%, and the content of the ternary material is 40%-90%. As an example, the content of the lithium manganate material can be, for example, 10%, 20%, 30%, 40%, 50%, 60%, etc. or within the range values composed of any two of the above values. Correspondingly, the content of the ternary material can be 40%, 50%, 60%, 70%, 80%, 90%, etc. or within the range values composed of any two of the above values. The research of this application finds that when the content of the lithium manganate material is within the above range, especially between 30%-60%, it can better balance the high energy density, rate performance, good safety and cycle performance of the battery.
[0084] It should be noted that the chemical formula of the ternary material in this application is LiNi x Co y Mn 1-x-y O 2 , 0.8 ≤ x < 1, 0 < y < 0.2. Selecting a high-nickel ternary material can ensure that the positive electrode active material has a high specific capacity. The chemical formula of the lithium manganate material in this application is LiNi a Mn 2-a O 4 , 0 ≤ a ≤ 0.2. Doping nickel elements in the lithium manganate structure can increase the capacity and improve the cycle performance.
[0085] In some embodiments, the lithium manganate material includes a single-crystal lithium manganate material, and the ternary material includes a single-crystal ternary material. The single-crystal material is selected because the crystal structure of the single-crystal material is highly ordered and there are no grain boundaries. Compared with polycrystalline materials, single-crystal materials are more stable during the charge and discharge cycle and are not prone to problems such as fracture, corrosion or peeling due to the existence of grain boundaries, which helps to improve the cycle stability and safety of the battery.
[0086] In some embodiments, based on the mass of the first positive electrode active material layer, the content of the carbon nanotubes is 0.1%-1.2%. As an example, the content of the carbon nanotubes can be 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1.1%, 1.2%, etc. or within the range values composed of any two of the above values; the diameter of the carbon nanotubes is 7nm-11nm. As an example, the diameter of the carbon nanotubes can be 7nm, 8nm, 9nm, 10nm, 11nm, etc. or within the range values composed of any two of the above values; the specific surface area of the carbon nanotubes is 200m 2 / g - 280m 2 / g. As an example, the specific surface area of the carbon nanotubes can be, for example, 200m 2 / g, 220m 2 / g, 240m 2 / g, 260m 2 / g, 280m 2 / g, etc. or within the range formed by any two of the above values. Carbon nanotubes that meet the above conditions can further ensure the conductivity and cycle performance of the battery.
[0087] X-ray diffraction (XRD) technology is widely used in the detection of positive electrode active materials. Through XRD analysis, the crystal structure type of the material and the occupancy and proportion of the elements in the material can be determined. In the XRD spectrum of the first positive electrode active material formed by mixing the ternary material with the lithium manganese oxide material of the present application, the characteristic peaks P of lithium manganese oxide appear at the positions of 2θ of 35°-38° and 42°-46°. 1 and P 2 , P 1 The crystal plane index is (311), P 2 The crystal plane index is (400), and the characteristic peaks P of the ternary material also appear at 2θ of 35°-38° and 42°-46°. 3 and P 4 , P 3 The crystal plane index is (101), P 2 The crystal plane index is (104). 1 The peak intensity is I 1 , P 2 The peak intensity is I 2 , P 3 The peak intensity is I 3 , P 4 The peak intensity is I 4 , and satisfy: 0.05≤I 1 ≤0.2,0.05≤I 2 ≤0.18, 0.1≤I 3 ≤0.25, 0.2≤I 4 ≤0.5. The present application has found that the first positive electrode active material having the above XRD diffraction peak characteristics can better balance the high energy density and rate, good safety and cycle performance of the battery.
[0088] As an example, I 1 It can be 0.05, 0.1, 0.15, 0.2, etc. or within the range of any two of the above values. 2 It can be 0.05, 0.08, 0.1, 0.13, 0.15, 0.18, etc. or within the range of any two of the above values. 3 It can be 0.1, 0.13, 0.15, 0.18, 0.2, 0.22, 0.25, etc. or within the range of any two of the above values. 4It can be 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, etc. or within a range formed by any two of the above values.
[0089] It is understandable that in high-power applications, the battery needs to be able to quickly provide a large current. The multi-pole structure distributes more contact points on the positive / negative electrode sheets of the battery, which helps to reduce the risk of current concentration at a single point, thereby improving the current carrying capacity and stability of the battery; and the multi-pole design can also effectively reduce the contact resistance between the battery and the external circuit, which is particularly important for high-power batteries, because low resistance can reduce energy loss and heat generation, and improve the efficiency and power output capacity of the battery; in addition, high-power batteries will generate more heat when working, and the multi-pole structure can provide more heat dissipation surfaces to help dissipate heat more effectively, thereby keeping the temperature of the battery within a controllable range, extending the battery life and ensuring safety; in addition, the multi-pole design can generally improve the mechanical strength and durability of the battery, especially when experiencing repeated charge and discharge cycles and vibration environments, it can reduce the risk of fatigue and damage to the connection parts, thereby extending the service life of the battery. Therefore, in order to ensure the uniformity of current distribution, reduce contact resistance, optimize thermal management, and improve the reliability and durability of the battery during high-power operation, in some embodiments of the present application, the lithium-ion secondary battery adopts a multi-pole winding structure.
[0090] For details about the positive electrode of this application, please refer to Figure 3 , which comprises a plurality of positive electrode ears 3, which are arranged at intervals along the length direction of the positive electrode sheet and protrude from the positive electrode current collector; the surface of the positive electrode current collector is coated with a positive electrode active material layer 1, and an insulating layer 2 is arranged on the positive electrode sheet. In the width direction of the positive electrode sheet, the insulating layer 2 is arranged along the side of the positive electrode sheet, and the insulating layer 2 and the plurality of positive electrode ears 3 are located on the same side of the positive electrode sheet, and the insulating layer 2 is adjacent to the positive electrode active material layer 1 but does not overlap. The surface of the positive electrode ear 3 is also covered with the insulating layer 2, and the head of the positive electrode ear 3 has an empty foil area, that is, the positive electrode ear 3 is only provided with an insulating layer 2 at its root (close to the connection between the positive electrode ear and the positive electrode current collector), and the head of the positive electrode ear 3 (far away from the connection between the positive electrode ear and the positive electrode current collector) is not provided with an insulating layer 2.
[0091] This can prevent the burrs on the positive electrode collector after die-cutting from short-circuiting with the negative electrode sheet, leading to battery failure. It can also prevent the positive electrode ear from short-circuiting with the negative electrode sheet due to the separator not completely covering the positive electrode sheet after winding, leading to battery failure.
[0092] like Figure 3 As shown, h 5 is the width of the positive electrode active material layer, h 3 +h 4 +h5 h is the projection of the width direction of the corresponding negative electrode paste on the positive electrode, 3 is the overhang area, i.e. the part of the negative electrode paste that exceeds the positive electrode paste in the width direction, h 4 To keep away from the overhang area of the positive ear, h 3 ≥2.5mm,h 4 ≥2.5mm,h 3 With h 4 Can be the same or different.
[0093] In some embodiments, along the length direction of the positive electrode ear, the length h of the insulating layer on the positive electrode ear is 1 Meet 4mm≥h 1 ≥2mm; along the width direction of the positive electrode sheet, the width of the insulating layer on the positive electrode collector is 4mm≥h 2 ≥0.5mm. This can better ensure that the battery will not fail due to short circuit between the positive and negative electrodes. As an example, h 1 It can be 2mm, 2.5mm, 3mm, 3.5mm, 4mm, etc. or within the range of any two of the above values. 2 It can be 0.5mm, 1mm, 2mm, 3mm, 4mm, etc., or within a range formed by any two of the above values.
[0094] Regarding the composition of the insulating layer, in some embodiments, based on the mass of the insulating layer, the insulating layer includes 70%-98% boehmite, 0%-20% alumina and 2%-10% binder. Boehmite has lower cost, lower hardness, less wear on machinery, and has a coating area of 1.5x1.5x1.5mm at the same weight. 2 O 3 1.25 times of that of Al 2 O 3 It can neutralize the free HF in the electrolyte, improve the acid resistance and safety performance of the battery. At the same time, in order to ensure that the insulating layer has good adhesion on the positive electrode collector, PVDF can be used as an adhesive.
[0095] In order to further improve the cycle performance of the battery, the positive electrode sheet of the present application can adopt a double-layer coating technology, that is, the positive electrode sheet also includes a second positive electrode active material layer, the first positive electrode active material layer is located between the positive electrode collector and the second positive electrode active material layer, and the second positive electrode active material layer includes a ternary material.
[0096] In some embodiments, the volume median diameter D of the lithium manganese oxide in the first positive electrode active material layer is 1 The volume median diameter D of the ternary material in the second positive electrode active material layer2 The ratio is 1.6-7.5, and D 1 8μm-15μm, D 2 The thickness of the nanostructured carbon fiber is 2μm-5μm, and this design can improve the battery cycle performance.
[0097] As an example, the volume median diameter D of lithium manganese oxide 1 It can be 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, etc. or within the range of any two of the above values. The volume median diameter D of the ternary material in the second positive electrode active material layer is 2 It can be 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, etc. or within the range of any two of the above values. 1 With D 2 The ratio is, for example, 1.6, 2.5, 4, 5.5, 6, 7.5, etc. or is within a range formed by any two of the above values.
[0098] In other embodiments, the first positive electrode active material layer and the second positive electrode active material layer may also simultaneously use a blended material of a ternary material and lithium manganese oxide. When the first positive electrode active material layer uses a ternary material blended with a capacity-type lithium manganese oxide, the capacity-type lithium manganese oxide has a higher manganese content, which can provide a larger capacity, which not only ensures that the battery energy density is not lost, but also reduces the contact between lithium manganese oxide and the electrolyte due to the presence of the ternary material, effectively inhibiting the dissolution of manganese elements in lithium manganese oxide; when the second positive electrode active material layer uses a ternary material blended with a high-temperature lithium manganese oxide, the high-temperature lithium manganese oxide has a smaller specific surface area, which can improve high-temperature cycle performance. High-temperature lithium manganese oxide can also improve structural stability by doping and / or coating metal elements.
[0099] It is worth noting that in this application, "capacitive lithium manganese oxide" can be understood as lithium manganese oxide doped with metal elements, and the range of the doping amount of the metal elements is between 100-500ppm; "high-temperature lithium manganese oxide" can be understood as lithium manganese oxide doped with metal elements, and the range of the doping amount of the metal elements is between 2000-3000ppm. Common metal elements include aluminum (Al), chromium (Cr), copper (Cu), zirconium (Zr), magnesium (Mg), cobalt (Co), and titanium (Ti). The capacity of capacity-type lithium manganese oxide is about 5-10% higher than that of high-temperature lithium manganese oxide.
[0100] In summary, if the first positive electrode active material layer uses ternary materials and capacity-type lithium manganese oxide, the energy density of the battery is improved, and the second positive electrode active material layer uses ternary materials and high-temperature lithium manganese oxide, which improves the stability and cycle performance of the battery in a high temperature environment. This design ensures that the battery can maintain a high energy output and a longer service life during long-term use.
[0101] In order to reduce the cost of the battery, the thickness of the first positive electrode active material layer is much greater than the thickness of the second positive electrode active material layer. For example, if the thickness of the first positive electrode active material layer is 40μm-100μm, then the thickness of the second positive electrode active material layer is 12μm-16μm. As an example, the thickness of the first positive electrode active material layer can be 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, etc., or within the range of any two of the above values, and the thickness of the second positive electrode active material layer can be 12μm, 13μm, 14μm, 15μm, 16μm, etc., or within the range of any two of the above values. It can be understood that in some embodiments, the ternary material in the first positive electrode active material layer and the second positive electrode active material layer uses the same material.
[0102] According to a second aspect of the present application, a lithium-ion secondary battery is provided, comprising a negative electrode sheet, a separator, an electrolyte, and the positive electrode sheet described in the first aspect of the present application.
[0103] It is understood that the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material. In some embodiments of the present application, the negative electrode active material includes graphite with a carbon coating layer, and the volume median diameter of the graphite is Dv50 G It is 10μm-25μm, for example, 10μm, 13μm, 15μm, 18μm, 20μm, 23μm, 25μm, etc. or is within the range formed by any two of the above values, thereby ensuring that the graphite negative electrode has a higher compaction density.
[0104] like Figure 4 As shown, it can be seen that there are no obvious gaps between the graphite particles. In other embodiments, the graphitization degree of the graphite is ≥ 93%. Graphite with a high graphitization degree has better electrical conductivity, thermal stability and mechanical strength, and can improve the performance and cycle life of the battery.
[0105] Please refer to Figure 5 , combined with JADE software, it can be seen that d002 ≥ 3.354nm, which indicates that amorphous carbon is coated on the graphite surface, which increases the overall interlayer spacing of the negative electrode material, thus facilitating Li + The carbon coating layer has a thickness of 0.1 mm to 1 mm, such as 0.1 mm, 0.3 mm, 0.5 mm, 0.7 mm, 1 mm, etc., or within a range of any two of the above values.
[0106] In order to improve the energy density of the battery, in some embodiments of the present application, the negative electrode active material may further include a silicon-based material, and the content of the silicon-based material is 0-10% based on the mass of the negative electrode active material. Specifically, the silicon-based material is SiC and / or SiO, the volume median diameter of the SiC is 5μm-12μm, and the volume median diameter of the SiO may be 4μm-10μm.
[0107] As an example, the blending amount of the silicon-based material can be 0%, 2%, 4%, 6%, 8%, 10%, etc., or within the range of any two of the above values. The volume median diameter of SiC can be, for example, 5 μm, 7 μm, 9 μm, 10 μm, 12 μm, etc., or within the range of any two of the above values. The volume median diameter of SiO can be, for example, 4 μm, 6 μm, 8 μm, 10 μm, etc., or within the range of any two of the above values.
[0108] In order to better improve the low temperature dynamics performance of the battery, in some embodiments of the present application, propyl propionate (PP) is added to the electrolyte, and the content W of propyl propionate in the electrolyte is 5%-60% based on the mass of the electrolyte. As an example, the content W of propyl propionate can be 5%, 10%, 15%, 20%, 30%, 40%, 50%, 60%, etc. or in the range of any two of the above values. Adding propyl propionate to the electrolyte can ensure that the electrolyte maintains good viscosity at low temperatures and ensures that lithium ions can migrate smoothly and freely.
[0109] In order to further improve the low temperature charge and discharge capability of the battery and improve the cycle life, the volume median diameter of graphite Dv50 G , the content of propyl propionate in the electrolyte W and the volume median diameter Dv50 of the positive electrode active material PAM Satisfy: R = Dv50 G *W / Dv50 PAM , 0.07≤R≤7.5, Dv50 G 10μm-25μm, 2μm≤Dv50 PAM ≤7μm.
[0110] It should be noted that when Dv50 PAM When Dv50 is smaller, the lithium ion diffusion path is short and the polarization is small. At the same time, the electrolyte is also easy to adhere to the surface of the original particles, reducing concentration polarization. PAM When it is too large, the lithium ion diffusion path is long. When the battery is working and discharging, the diffusion of lithium ions from the negative electrode to the positive electrode cannot compensate for the electrons flowing from the negative electrode into the positive electrode in time, resulting in excess electrons in the positive electrode, causing the electrode potential to shift negatively, causing the discharge voltage platform to become lower or even unable to discharge.
[0111] It is worth noting that when the positive electrode sheet includes two layers of positive electrode active material, the Dv50 in this application is PAM It refers to the volume median diameter of the positive electrode active material in the first positive electrode active material layer. This is because the second positive electrode active material layer is thinner and has less impact.
[0112] As an example, the value of R can be 0.07, 0.5, 1, 2, 3, 4, 5, 6, 7.5, etc., or within the range of any two of the above values; the volume median diameter Dv50 of graphite G It can be 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, etc., or be within a range formed by any two of the above values.
[0113] In order to ensure high-power discharge characteristics while ensuring the cycle performance of the battery, a large-pore diaphragm is used in some embodiments of the present application. The permeability of the diaphragm is 70sec / 100cc-170sec / 100cc, for example, it can be 70sec / 100cc, 100sec / 100cc, 130sec / 100cc, 150sec / 100cc, 170sec / 100cc, etc., or within the range formed by any two of the above values. The porosity of the diaphragm is 40%-50%, for example, it can be 40%, 42%, 45%, 48%, 50%, etc., or within the range formed by any two of the above values.
[0114] Specifically, the diaphragm includes a base membrane, the pore size of the base membrane is 32nm-58nm, for example, it can be 32nm, 35nm, 38nm, 42nm, 45nm, 48nm, 52nm, 55nm, 58nm, etc. or within the range formed by any two of the above values. A coating layer and a ceramic layer are stacked on the surface of one side of the base membrane, the ceramic layer includes boehmite and / or alumina, and the ceramic layer is located between the base membrane and the coating layer.
[0115] Further, the coating layer includes polyvinylidene fluoride (PVDF) and polymethyl methacrylate (PMMA) in a mass ratio of 1:9-9:1, and the mass ratio of PVDF to PMMA can be 1:9, 3:7, 5:5, 7:3, 9:1, etc., or within the range formed by any two of the above values; wherein, the volume median diameter of PVDF is 0.3μm-2.5μm, for example, 0.3μm, 0.7μm, 1μm, 1.5μm, 2μm, 2.5μm, etc., or within the range formed by any two of the above values, and the volume median diameter of PMMA is 0.1μm-0.2μm, for example, 0.1μm, 0.12μm, 0.15μm, 0.18μm, 0.2μm, etc., or within the range formed by any two of the above values. The thickness H of the coating layer and the area ratio S of the coating layer on the base film satisfy: Q = H / S, 0.7 ≤ Q ≤ 15, H is 0.5 μm-3 μm, S is 20%-70%. The coating layer designed in this way not only has excellent porosity and can meet the requirements of high-power discharge, but also exhibits good adhesion performance in the battery, thereby ensuring the cycle performance of the battery. As an example, the thickness H of the coating layer can be 0.5 μm, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, etc. or within the range of any two of the above values, the area ratio S of the coating layer on the base film can be, for example, 20%, 30%, 40%, 50%, 60%, 70%, etc. or within the range of any two of the above values, and the value of Q can be 0.7, 2, 4, 6, 8, 10, 12, 15, etc. or within the range of any two of the above values.
[0116] It should be noted that the above is the front structure of the diaphragm, and only the rubber coating layer is set on the back of the diaphragm. Figure 6 ,in Figure 6 a is the front structure of the diaphragm, Figure 6 b is the reverse structure of the diaphragm.
[0117] In some embodiments of the present application, the electrolyte includes 10%-20% lithium salt, 60%-80% organic solvent and 1%-5% additives based on the mass of the electrolyte. As an example, the lithium salt includes lithium hexafluorophosphate (LiFP 6 ), lithium tetrafluoroborate (LiBF 4), lithium bis(oxalatoborate) (LiBOB), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(fluorooxalatoborate) (LiODFB), lithium bis(fluorosulfonyl)imide (LiFSI); the organic solvent includes at least one of propyl propionate (PP), ethyl propionate (EP), ethyl difluoroacetate (EDFA), ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC); to ensure the film formation stability of the battery material, the additive includes at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC), 1,3-propane sultone (1,3-PS). The present application uses an electrolyte formed by a low-cost solvent and a lithium salt, which has good ionic conductivity, a stable electrochemical window and a long cycle life while reducing the cost of the electrolyte.
[0118] In summary, the lithium-ion secondary battery composed of the above-mentioned positive electrode sheet, negative electrode sheet, separator and electrolyte has high power discharge characteristics, excellent electrochemical performance and good low-temperature charge and discharge capabilities, and can also significantly reduce battery costs.
[0119] The present application is further described in detail below in conjunction with specific examples, which should not be construed as limiting the scope of protection claimed in the present application. In all examples and comparative examples of the present application, the unit % represents the mass percentage content.
[0120] Example 1
[0121] This embodiment provides a method for preparing a lithium-ion secondary battery, comprising the following steps:
[0122] (1) Preparation of positive electrode
[0123] The single crystal ternary material (chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O 2 ) and single crystal lithium manganese oxide (chemical formula LiMn 2 O 4 ) are mixed uniformly in a mass ratio of 7:3 to form a positive electrode active material, and its Dv50 PAM is 5.1 μm, Dv99 is 24.5 μm, and the XRD spectrum of the positive electrode active material is shown in Figure 7-Figure 9 (The spectrum is normalized with the highest peak intensity as the denominator). It can be seen from the figure that a characteristic peak P appears at 2θ of 35°-38°. 1 and P 3 And the characteristic peak P appears at 42°-46° 2 and P 4 , P 1Peak intensity I 1 =0.127, P 2 Peak intensity I 2 =0.139, P 3 Peak intensity I 3 =0.2, P 4 Peak intensity I 4 =0.4.
[0124] The positive electrode active material, conductive carbon black and binder PVDF were uniformly dispersed in N-methylpyrrolidone at a mass ratio of 98.5:0.5:1 to obtain a uniform slurry. Carbon nanotubes (length 5.3 μm, tube diameter 7 nm, specific surface area 240 m 2 / g, volume median diameter 1μm), the amount of which accounts for 0.5% of the total mass of the positive electrode active material layer, and the solid content of the final positive electrode slurry is controlled at 70%. Subsequently, the positive electrode slurry is evenly coated on both surfaces of the aluminum foil, and dried and rolled in sequence to finally obtain a positive electrode sheet. Ceramic glue (composed of 80% boehmite, 10% alumina and 10% binder PVDF in a mass ratio) is coated on the ear end of the positive electrode sheet, so that the formed insulating layer is connected to the positive electrode active material layer on one side in the width direction but does not overlap, and the other end extends to the root of the positive ear. The length of the insulating layer on the positive ear is h 1 =2.5mm, the width of the insulating layer on the positive electrode collector h 2 =0.8mm.
[0125] (2) Preparation of negative electrode sheet
[0126] The negative electrode active material, binder SBR, thickener CMC and conductive carbon black are dispersed in deionized water in a mass ratio of 96:1.5:1:1.5 to obtain a uniform negative electrode slurry with a solid content of 50%. The negative electrode slurry is evenly coated on both surfaces of the copper foil, and the negative electrode sheet is obtained after drying and rolling. The negative electrode active material is composed of 95% graphite with a carbon coating layer and 5% silicon carbide, the volume median diameter of the silicon carbide is 10μm, the graphitization degree of the graphite is ≥93%, and the volume median diameter of the graphite is Dv50 G The thickness of the carbon coating layer is 0.5 mm.
[0127] (3) Selection of diaphragm
[0128] A large-pore diaphragm is used, the pore size of the base membrane is between 45-58nm, the surface of the base membrane is coated with a boehmite ceramic layer and a water-based adhesive layer, the adhesive layer is a mixture of water-based PVDF (volume median diameter 0.3μm) and PMMA (volume median diameter 0.2μm) in a mass ratio of 5:5, the coating layer coverage is 30%, and the coating layer thickness is 1.5μm. The air permeability of the diaphragm is 70sec / 100cc, and the porosity of the diaphragm is 45%.
[0129] (4) Preparation of electrolyte
[0130] LiFP 6 , PP, DMC and FEC are uniformly mixed in a mass ratio of 15:60:22:3 to form an electrolyte.
[0131] (5) Preparation of batteries
[0132] The positive electrode sheet and the negative electrode sheet prepared above are subjected to the steps of slitting, sheet making, winding, packaging, baking, liquid injection, formation and capacity division to obtain a multi-electrode winding lithium-ion secondary battery.
[0133] The preparation methods of the lithium ion secondary batteries in Examples 2 to 9 are the same as those in Example 1, with the differences being shown in Table 1.
[0134] Table 1
[0135]
[0136]
[0137] Example 10
[0138] The positive electrode sheet adopts double-layer coating technology. The first positive electrode active material layer uses the same positive electrode active material as that in Example 1, wherein the volume median diameter D of lithium manganese oxide is 1 15μm, thickness 100μm;
[0139] The second positive electrode active material layer has a volume median diameter D 2 2μm ternary material (chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O 2 ), the thickness is 12μm.
[0140] The remaining steps and process parameters are the same as those in Example 1.
[0141] Embodiment 11
[0142] The positive electrode sheet adopts double-layer coating technology. The first positive electrode active material layer uses the same positive electrode active material as that in Example 1, wherein the volume median diameter D of lithium manganese oxide is 112μm;
[0143] The thickness of the second positive electrode active material layer is 60 μm, and the volume median diameter D 2 The ternary material (chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O 2 ), the thickness is 15μm.
[0144] The remaining steps and process parameters are the same as those in Example 1.
[0145] Example 12
[0146] The positive electrode sheet adopts double-layer coating technology. The first positive electrode active material layer uses the same positive electrode active material as that in Example 1, wherein the volume median diameter D of lithium manganese oxide is 1 8μm, thickness 40μm;
[0147] The second positive electrode active material layer has a volume median diameter D 2 5μm ternary material (chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O 2 ), the thickness is 16μm.
[0148] The remaining steps and process parameters are the same as those in Example 1.
[0149] Embodiment 13
[0150] The positive electrode sheet adopts double-layer coating technology, and the first positive electrode active material layer uses 70% ternary material (chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O 2 ) mixed with 30% capacity type lithium manganese oxide (chemical formula LiMg 0.001 Mn 1.999 O 4 ) of positive electrode active material, with a thickness of 70 μm;
[0151] The second positive electrode active material layer is 60% ternary material (chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O 2 ) mixed with 40% high temperature lithium manganese oxide (chemical formula LiMg 0.05 Mn 1.95 O 4 ,)'s positive electrode active material has a thickness of 14 μm.
[0152] The remaining steps and process parameters are the same as those in Example 1.
[0153] The preparation methods of the lithium ion secondary batteries in Examples 14 to 21 are the same as those in Example 1, except for the differences shown in Table 2.
[0154] Table 2
[0155] <![CDATA[Dv50 G (μm)]]> W R H(μm) S Q Embodiment 14 15 6.8% 0.2 1.5 30% 5.0 Embodiment 15 25 60% 2.94 1.5 30% 5.0 Example 16 58.7 33% 3.8 1.5 30% 5.0 Embodiment 17 76.5 50% 7.5 1.5 30% 5.0 Embodiment 18 10 60% 1.18 3 0.3 10 Embodiment 19 10 60% 1.18 3 0.2 15 Embodiment 20 10 60% 1.18 0.5 0.7 0.7 Embodiment 21 10 60% 1.18 1 0.4 2.5
[0156] Comparative Example 1
[0157] The difference from Example 1 is that this comparative example only uses ternary materials as positive electrode active materials, and its XRD spectrum is shown in Figure 7-Figure 9 (The spectrum is normalized using the highest peak intensity as the denominator).
[0158] It can be seen from the figure that a characteristic peak P appears at the position of 2θ 35°-38° 3 And the characteristic peak P appears at 42°-46° 4 , P 3 Peak intensity I 3 =0.32, P 4 Peak intensity I 4 =0.60.
[0159] Comparative Example 2
[0160] The difference from Example 1 is that this comparative example uses only lithium manganate as the positive electrode active material.
[0161] Comparative Example 3
[0162] The difference from Example 1 is that the particle size Dv50 of the positive electrode active material in this comparative example is PAM is 1.9μm, then A is 12.9.
[0163] Comparative Example 4
[0164] The difference from Example 1 is that in this comparative example, the particle size Dv99 of the positive electrode active material is 10.2 μm, and A is 2.
[0165] Comparative Example 5
[0166] The difference from Example 1 is that the length L of the carbon nanotubes in this comparative example is 32 μm.
[0167] Comparative Example 6
[0168] The difference from Example 1 is that the length L of the carbon nanotubes in this comparative example is 4 μm.
[0169] Test Case
[0170] 1. Particle size test
[0171] Choose ultrapure water as the dispersion medium, add 1g of the sample to be tested into 1L of the dispersion medium, and ultrasonicate for 60 minutes to fully disperse the sample to form a uniform suspension or dispersion. Pour the prepared sample suspension or dispersion into the sample pool, turn on the laser particle size analyzer for testing, and after the test is completed, the computer will generate a particle size distribution diagram and related data report.
[0172] 2. Coating thickness test
[0173] The electrode after coating roller pressing is measured with a micrometer, and 10 positions are randomly selected on the electrode for testing. The average of the 10 data after the test is the thickness H of the electrode. 1 Measure the thickness H of the current collector before coating using a micrometer as described above. 2 , then the coating thickness is H 1 -H 2 .
[0174] 3. Compaction density test
[0175] Compacted density = (total weight of pole piece - weight of current collector) / [pole piece area*(pole piece thickness - current collector thickness)].
[0176] 4. XRD test
[0177] The model of XRD diffractometer was BrukerD8 Advance, and Highscore software was used to refine the XRD patterns after testing (Rietvald method).
[0178] 5. Volume energy density test
[0179] The lithium-ion secondary battery is charged to full capacity at constant current and constant voltage at 25°C, and then discharged to 3V at 0.2C. The released capacity is recorded as the discharge capacity (also called battery capacity), and the released energy is recorded as the discharge energy. The average discharge voltage is calculated as discharge energy / discharge capacity.
[0180] The lithium-ion secondary battery was charged to 30% SOC at 25°C and the battery thickness was tested using 600g PPG.
[0181] Calculate volume energy density = battery capacity * platform voltage / battery length / width / thickness.
[0182] 6. Low temperature discharge performance test
[0183] The lithium-ion secondary battery is charged to full charge at constant current and constant voltage at 25°C, and then discharged to 3V at 0.2C. The discharged capacity is recorded as the initial discharge capacity. The lithium-ion secondary battery is charged to full charge at constant current and constant voltage at 25°C, and then placed in a low-temperature box at -20°C. After leaving for 2 hours, it is discharged to 3V at 10C. The discharged capacity is recorded as the final discharge capacity. Low-temperature discharge capacity retention rate = final discharge capacity / initial discharge capacity*100%.
[0184] 7. Cycle performance test
[0185] The lithium-ion battery was subjected to a 1C / 5C cycle test at 35°C, specifically: 1C charge to 4.2V, 0.05C cutoff, 5C discharge to 3V, repeated 500 times, and 0.2C charge to 4.2V, 0.05C cutoff, 0.2C discharge to 3V every 100 cycles, and the capacity retention rate and thickness expansion rate after 500 cycles were tested.
[0186] 500-week capacity retention rate = remaining capacity / initial capacity*100%.
[0187] 8. Overcharge performance test
[0188] Perform a 2C-5V overcharge test on lithium-ion secondary batteries at 25°C: After the battery is discharged at 0.5C, it is charged to 5V with a 2C overcharge current and then switched to a constant voltage for 7 hours or the temperature is lowered to room temperature.
[0189] 9. Furnace temperature test
[0190] The lithium-ion secondary battery was charged at 25°C and charged to the upper limit voltage at 0.5C. The battery was placed in an incubator, and the temperature of the incubator was increased to 140°C±2°C at a rate of 5°C / min, and this temperature was maintained for 60 minutes.
[0191] The above test results are shown in Table 3, and the cycle retention rate curve is shown in Fig.10 .
[0192] Table 3
[0193]
[0194]
[0195] It can be seen from Table 3 that after the positive electrode active material formed by mixing an appropriate amount of lithium manganese oxide in the ternary material is rolled, the compaction density of the obtained positive electrode sheet is relatively large. Taking Example 1 as an example, its compaction density can reach 3.25g / cm 3, while the battery thickness increases slightly, and the average discharge voltage increases, thereby ensuring that the energy density of the battery in Examples 1-21 is not lost. Compared with Example 1, Comparative Example 2 uses 100% lithium manganese oxide as the positive electrode active material, which greatly increases the battery thickness and significantly loses the volume energy density of the battery. The particle size A value of the positive electrode active material in Comparative Examples 3-4 exceeds the range of 2.14-12.5, resulting in a poor stacking effect between the positive electrode active material particles, thereby affecting the compaction density of the positive electrode sheet and reducing the volume energy density of the battery.
[0196] Under -20°C conditions, all examples 10C discharge can release more than 90.5% of the capacity, indicating that the low-temperature discharge performance of the battery is significantly improved after the addition of lithium manganese oxide. This is due to the specific chemical structure of lithium manganese oxide, which enables the positive electrode material to maintain good ion conduction and electron transfer performance in a low temperature environment. In contrast, although the ternary lithium-ion battery of Comparative Example 1 has advantages in energy density, its ion conduction is more affected under low temperature conditions, which is not conducive to the discharge performance of the battery. The particle size A value of the positive electrode active material in Comparative Examples 3-4 exceeds the range of 2.14-12.5, resulting in poor contact between the positive electrode active material particles, thereby affecting the lithium ion transmission rate and causing the discharge capacity of the battery to decrease.
[0197] Combination Fig.10 It can be seen that due to the existence of the Jahn-Taller effect, manganese will continue to dissolve. Therefore, in Comparative Example 2, the battery swells and the capacity drops after only 350T of cycling at 35°C, while the capacity retention rate of all embodiments still reaches more than 90% after 500T of cycling. This shows that the blending of lithium manganese oxide and ternary materials makes up for the defects of lithium manganese oxide materials, improves the structural stability of the materials, and thus improves the high-temperature cycle stability of the battery. In Comparative Examples 3-4, the particle size A value of the positive electrode active material exceeds the range of 2.14-12.5, resulting in poor contact between the positive electrode active material particles, thereby affecting the lithium ion transmission rate and causing the battery's cycle performance to decline. In Comparative Examples 5-6, the length of the carbon nanotubes exceeds the range of 5-30μm, which increases the positive electrode sheet resistance and affects the lithium ion transmission rate, thereby causing the battery's cycle performance to decline.
[0198] The safety performance of the blended material of ternary material and lithium manganese oxide is significantly improved compared with the pure ternary material. The safety performance of all embodiments is equivalent to that of Comparative Example 2, and all can pass 2C-5V overcharge and 140°C furnace temperature. Since the amount of oxygen released by lithium manganese oxide during charging and discharging is relatively small, the possibility of gas accumulation inside the battery is reduced, thereby reducing the risk of gas explosion inside the battery. In addition, the blended material has better overcharge resistance under high-voltage charging than traditional nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) materials, which means that when charging, even if the battery is charged to a higher voltage, the blended material can maintain the stability of the material structure and reduce the safety risks during charging. The particle size A value of the positive active material in Comparative Examples 3-4 exceeds the range of 2.14-12.5, causing the ternary material particles in the positive electrode sheet to aggregate, resulting in a decrease in the thermal stability of the battery.
[0199] It can be seen that the present application can prepare lithium-ion secondary batteries with high-power discharge characteristics, excellent electrochemical properties and good low-temperature charge and discharge capabilities, while reducing the cost of battery materials, providing a new and more competitive battery solution for electric vehicles, energy storage systems and other fields.
[0200] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection created by this application.
Claims
1. A positive electrode sheet, comprising a positive electrode current collector and a first positive electrode active material layer disposed on at least one side surface of the positive electrode current collector, wherein the first positive electrode active material layer comprises a first positive electrode active material, a conductive agent and a binder; characterized in that: The first positive electrode active material includes a lithium manganate material and a ternary material. The particle size A of the first positive electrode active material satisfies: 2.14≤A≤12.5 and A=Dv99 / Dv50 PAM , among which, Dv50 PAM It is the particle size corresponding to the cumulative volume distribution percentage of the first positive electrode active material reaching 50%, 2μm≤Dv50 PAM ≤7μm; Dv99 is the particle size corresponding to when the cumulative volume distribution percentage of the first positive electrode active material reaches 99%, 15μm≤Dv99≤25μm; The conductive agent includes carbon nanotubes, and the length L of the carbon nanotubes satisfies: 5 μm≤L≤30 μm.
2. The positive electrode sheet according to claim 1, characterized in that: Based on the mass of the first positive electrode active material, the content of the lithium manganate material is 10%-60%, preferably 30%-60%; Preferably, the chemical formula of the lithium manganese oxide material is LiNi a Mn 2-a O4, 0≤a≤0.2; Preferably, the lithium manganese oxide material comprises a single crystal lithium manganese oxide material; Preferably, based on the mass of the first positive electrode active material, the content of the ternary material is 40%-90%, preferably 40%-70%; Preferably, the chemical formula of the ternary material is LiNi x Co y Mn 1-x-y O2, 0.8≤x<1, 0 <y<0.2; Preferably, the ternary material comprises a single crystal ternary material.
3. The positive electrode sheet according to claim 1, characterized in that: Based on the mass of the first positive electrode active material layer, the content of the carbon nanotubes is 0.1%-1.2%, preferably 0.1%-0.5%; Preferably, the diameter of the carbon nanotubes is 7nm-11nm; Preferably, the specific surface area of the carbon nanotubes is 200 m 2 / g-280m 2 / g; Preferably, the XRD spectrum of the first positive electrode active material shows characteristic peaks P1 and P3 at 2θ of 35°-38° and characteristic peaks P2 and P4 at 2θ of 42°-46°, and the peak intensities of P1, P2, P3 and P4 are I1, I2, I3 and I4, respectively, and satisfy: 0.05≤I1≤0.2, 0.05≤I2≤0.18, 0.1≤I3≤0.25, 0.2≤I4≤0.
5.
4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The positive electrode sheet further includes a second positive electrode active material layer, the first positive electrode active material layer is located between the positive electrode collector and the second positive electrode active material layer, and the second positive electrode active material layer includes a ternary material.
5. The positive electrode sheet according to claim 4, characterized in that: The ratio of the volume median diameter D1 of the lithium manganate material in the first positive electrode active material layer to the volume median diameter D2 of the ternary material in the second positive electrode active material layer is 1.6-7.5, and D1 is 8 μm-15 μm, and D2 is 2 μm-5 μm; Preferably, the ratio of the thickness of the second positive electrode active material layer to the thickness of the first positive electrode active material layer is 0.12-0.4; Preferably, the thickness of the first positive electrode active material layer is 40 μm-100 μm; Preferably, the second positive electrode active material layer has a thickness of 12 μm-16 μm.
6. A lithium ion secondary battery, characterized in that: Comprising a negative electrode sheet, a separator, an electrolyte and a positive electrode sheet according to any one of claims 1 to 5; Preferably, the negative electrode sheet comprises a negative electrode active material, and the negative electrode active material comprises graphite having a carbon coating layer; The graphitization degree of the graphite is ≥ 93%, and / or the volume median diameter Dv50 of the graphite is G The thickness of the carbon coating layer is 10 μm-25 μm, and / or the thickness of the carbon coating layer is 0.1 mm-1 mm.
7. The lithium ion secondary battery according to claim 6, characterized in that: The lithium-ion secondary battery comprises a multi-electrode winding structure; And / or, the negative electrode active material further comprises a silicon-based material, and the content of the silicon-based material is 0-10% based on the mass of the negative electrode active material; Preferably, the silicon-based material is SiC and / or SiO, the volume median diameter of the SiC is 5 μm-12 μm, and / or the volume median diameter of the SiO is 4 μm-10 μm.
8. The lithium ion secondary battery according to claim 6 or 7, characterized in that: The electrolyte includes propyl propionate. Based on the mass of the electrolyte, the content W of the propyl propionate is 5%-60%, and satisfies: R=Dv50 G *W / Dv50 PAM , 0.07≤R≤7.5, 2μm≤Dv50 PAM ≤7μm; Dv50 G 10μm-25μm; And / or, the diaphragm includes a base film, a ceramic layer and a coating layer are stacked on one side surface of the base film, and the ceramic layer is located between the base film and the coating layer.
9. The lithium ion secondary battery according to claim 8, characterized in that: The coating layer comprises polyvinylidene fluoride and polymethyl methacrylate in a mass ratio of 1:9-9:1, and the thickness H of the coating layer and the area ratio S of the coating layer on the base film satisfy: Q=H / S, 0.7≤Q≤15, H is 0.5μm-3μm, S is 20%-70%, preferably S is 30%-40%; Preferably, the volume median diameter of the polyvinylidene fluoride is 0.3 μm-2.5 μm; Preferably, the volume median diameter of the polymethyl methacrylate is 0.1 μm-0.2 μm.
10. The lithium ion secondary battery according to claim 8, characterized in that: The porosity of the diaphragm is 40%-50%; And / or, the air permeability of the diaphragm is 70sec / 100cc-170sec / 100cc; and / or, the pore size of the basement membrane is 32nm-58nm, preferably 45nm-58nm; And / or, the ceramic layer comprises boehmite and / or alumina.
Citation Information
Patent Citations
Positive electrode for lithium ion secondary battery, and lithium ion secondary battery
CN109428083A
Positive electrode for lithium secondary battery, and lithium secondary battery comprising same
CN113474912A
Positive pole piece as well as electrochemical device and electronic device comprising positive pole piece
CN113892199A
Secondary battery and electronic device
CN118431399A
Battery cell, battery, and electrical device
WO2024207655A1
Cited By
Positive plate and lithium ion secondary battery
CN120072849A